Bioethics in a European Perspective - Have, Henk ten; Gordijn, Bert (International Library of Ethics, Law, and the New Medicine, 2001)
In this book, developed by a group of collaborating scholars in bioethics from different European countries, an overview is given of the most salient themes in present-day bioethics. The themes are discussed in order to enable the reader to have an in-depth overview of the state of the art in bioethics. Introductory chapters will guide the reader through the relevant dimensions of a particular area, while subsequent case discussions will help the reader to apply the ethical theories to specific clinical problems and health policy queries. The book focuses on perspectives typical for the European context. This highlights not only particular bioethical themes such as social justice, choices in health care, and health policy (e.g., in post-communist countries), it also emphasizes specific approaches in ethical theory, in relation to Continental philosophies such as phenomenology and hermeneutics. Because of its articulation of what is typical for the European health care setting as well as for bioethical debate, this book is unique in comparison to existing textbooks in bioethics. The book is an introductory textbook acquainting the reader with the major issues in present-day health care as well as the various theoretical and practical approaches to clarify these issues